Interrelationship between morphological, agronomic and molecular characteristics in the analysis of common bean genetic diversity - Guidoti, David Teixeira; Gonela, Adriana; Vidigal, Maria Celeste Gonçalves; Conrado, Thiago Vincenzi; Romani, Isaac (Acta Scientiarum. Agronomy, 2018)
The present study aimed to analyze, through 12 morpho-agronomic traits and 18 micro satellite loci, the genetic diversity in 17 common bean accessions from the Bean Germplasm Bank of the Center for Applied Agricultural Research of the State University of Maringá (BGF/Nupagri/UEM), in Paraná State, Brazil. Genetic diversity was assessed by joint analysis of phenotypic and genotypic characteristics using the Genetics platform of SAS software. To that end, a dissimilarity matrix was constructed based on the Jaccard index. This was used to generate a dendrogram via UPGMA hierarchical clustering, validated by multidimensional scaling and nonorthogonal principal components analysis. Based on genetic diversity analysis, the accessions were clustered into two large groups: one consisting of 11 accessions of Andean origin and the other containing six Mesoamerican accessions. The 17 accessions from the BGF/Nupagri/UEM were found to be an important source of genetic variability for inclusion in common bean breeding programs, contributing to the development of cultivars with desirable agronomic characteristics.